The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fsurg.2021.637180
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Vulvo-Perineal Endometriosis: A Systematic Review

Abstract: Objective: To describe the available knowledge on vulvo-perineal endometriosis including its diagnosis, clinical management and recurrence rate.Methods: We followed the PRISMA guidelines for Systematic Reviews and our study was prospectively registered with PROSPERO (CRD42020202441). The terms “Endometriosis” and “Perineum” or “Vulva” were used as keywords. Cochrane Library, Medline/Pubmed, Embase and Clinicaltrials.gov were searched. Papers in English, Spanish, Portuguese, French or Italian from inception to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 116 publications
(148 reference statements)
1
15
0
Order By: Relevance
“…Iatrogenic implantation of endometrial tissue into the open wound at perineum has been proposed as the predominant theory in relation to the genesis of PEM [ 11 ]. A recent systemic review incorporating 90 studies found that 95.3% of 283 patients with vulvo-perineal endometriosis had gone through perineal trauma before the onset of symptoms [ 5 ]. The results of our survey further corroborate the hypothesis of iatrogenic seeding through wound contact with viable endometrial cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Iatrogenic implantation of endometrial tissue into the open wound at perineum has been proposed as the predominant theory in relation to the genesis of PEM [ 11 ]. A recent systemic review incorporating 90 studies found that 95.3% of 283 patients with vulvo-perineal endometriosis had gone through perineal trauma before the onset of symptoms [ 5 ]. The results of our survey further corroborate the hypothesis of iatrogenic seeding through wound contact with viable endometrial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Perineal endometriosis (PEM) is a rare type that accounts for merely 0.17% to 0.37% of women treated for endometriosis [ 3 , 4 ]. Characterised by the ectopic endometrial tissue located in the subcutaneous adipose layer of perineum, PEM is predominantly associated with injuries caused by episiotomy or obstetrical tears [ 5 7 ]. Patients with PEM typically show solid tender nodule or mass with cyclic pain around the perineal scar [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very few cases have been reported in the literature, and in most of these case reports either concomitant pelvic disease is present or it is undetermined whether more extensive disease is present as laparoscopy was not performed [3][4][5][6]. In one systematic review, it was noted that 95.3% of patients presenting with vulvo-perineal endometriosis have undergone either episiotomy, perineal trauma, vaginal injury, or vaginal surgery [7]. In most cases, patients presented with cyclical vulvar pain, and were initially thought to have a Bartholin gland cyst.…”
Section: Discussionmentioning
confidence: 99%